Province of Alberta, Canada : resources and development - Alberta. Department of Economic Affairs
This is a map of economic development of Alberta in 1952 showing crude oil and natural gas fields and pipelines, forest, parkland and prairie areas, mineral resources disposition, pulpwood and timber fields, grazing lands, crop fields, water power plants, steam generator plants, power lines, major waterways, irrigation areas, First Nations reserves, forest reserves, national parks, railways, cities and towns. Inset: [Regional map of Alberta]. Scale 1:1,267,200, or 20 miles to 1 inch. Relief shown by spot heights. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Shows crude oil and natural gas fields and pipelines, forest, parkland and prairie areas, mineral resources disposition, pulpwood and timber fields, grazing lands, crop fields, water power plants, steam generator plants, power lines, major waterways, irrigation areas, First Nations reserves, forest reserves, national parks, railways, cities and towns.